Aportes para el estudio de la entomología venezolana en la obra lingüística de Lisandro Alvarado (Revista Electrónica REDINE, 2021)
Dr. Lisandro Alvarado is recognized for his work in the field of humanities and science, particularly for his linguistic and ethnographic research. In the field of science, his articles on medicine have stood out, but his texts as a naturalist have been little disseminated and less studied. In this work, attention is focused on an uninvestigated aspect of its lexicographic production, the words that refer to insects and other arthropods. The entomological terms present in the fundamental work of Alvarado Alvarado Glosario de Voces Indígenas de Venezuela, Glosarios del Bajo Español en Venezuela y Notas de Historia Natural are analyzed and systematized on the basis of a four-dimensional profile: the linguistic, scientific, referential and ethnographic. His contribution to the knowledge of the entomofauna of country is determined and his pioneering contribution to the cultural and systematic entomology of Venezuela is demonstrated.
Keywords: science history; cultural entomology; venezuelan positivism